The Influence of Debt to Asset Ratio (DAR) on Stock Prices in Foot and Beverage Companies Listed on Bursa Egek Indonesia - Burhan Rifuddin (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This research is raining to analyze the effect on stock prices. The company's financial information includes Debt to Asset Ratio (DAR), an independent variable that is suspected to affect the stock price at the company, where the stock price is the dependent variable. The population in this study are all financial statements of Food and Beverage companies listed on the Indonesia Stock Exchange, audited and published. The sample is the financial statements of Food and Beverage companies period 2012-2016 taken through a purposive sampling of nine companies. Data collection is done by documentation technique. The analysis technique used is classical assumption test and simple regression analysis. Based on The Results, regression coefficient analysis shows the Debt to Asset Ratio (DAR) coefficient of 8610, 496, which is positive for stock prices and a significant value of 0.292 where this value indicates that the relationship between the Debt to Asset Ratio (DAR) variable to the stock price has no significant negative effect because 0.0292 is greater than> 0.05 or 5%. So the hypothesis in this study states that the Debt to Asset Ratio (DAR) has a significant negative effect on stock prices Test results. The coefficient of determination in the Summary Model test results table shows that the R Square value is 0.025 where this value implies that the influence of Debt to Asset Ratio (DAR) on Stock Prices is 2.5%, while 97.5% Share Prices are influenced by variables others who were not examined in this study. 292, where this value indicates that the relationship between the Debt to Asset Ratio (DAR) variable to the stock price has no significant negative effect because 0.0292 is greater than> 0.05 or 5%. So the hypothesis in this study states that the Debt to Asset Ratio (DAR) has a significant negative effect on stock prices Test results. The coefficient of determination in the Summary Model test results table shows that the R Square value is 0.025 where this value implies that the influence of Debt to Asset Ratio (DAR) on Stock Prices is 2.5%, while 97.5% Share Prices are influenced by variables others who were not examined in this study. 292, where this value indicates that the relationship between the Debt to Asset Ratio (DAR) variable to the stock price has no significant negative effect because 0.0292 is greater than> 0.05 or 5%. So the hypothesis in this study states that the Debt to Asset Ratio (DAR) has a significant negative effect on stock prices Test results. The coefficient of determination in the Summary Model test results table shows that the R Square value is 0.025 where this value implies that the influence of Debt to Asset Ratio (DAR) on Stock Prices is 2.5%, while 97.5% Share Prices are influenced by variables others who were not examined in this study.